Collective Action and Rural Development: Quality Organization Institutions - Macías Vázquez, Alfredo (Cooperativismo & Desarrollo, 2016)
Purpose: from an institutional approach, this article intends to start a debate by analyzing the most representative collective action institutions for quality organization at the territorial level, where quality certification processes are conducted to allow local communities to build certain market power and thus fix the value generated in the same territory. Description: it is also analyzed how the gaps at the level of cooperation relationships among stakeholders condition the potentiality of these institutions when facing challenges with respect to sustainable rural development in globalization. Point of view: academic literature pays little attention to the analysis of collective action of common intangible assets in local communities. Conclusions: collective quality organization represents an important collective actor for the purpose of strategically guiding the technological innovation process, with all the economic and institutional consequences this entails. If we truly manage to have a cooperative organization of this kind that takes a leading role in the diffusion of technological innovations, we will surely be in a position to think of and plan more effective and comprehensive rural development strategies.